Cultural patronage: State, power, and financing of artistic expressions - Baranchuk, Mariana (2007)
Capital funding has participated, in confluence with the State, in the promotion of products for the cultural market since the ancient times up to nowadays. This work looks into the relationship that the economical power, the State, and the artistic expressions have maintained through different historical moments; insinuating that this linkage, as well as the connection to the artists (and/or cultural workers), affects the work itself, not only in its symbolic dimension, as a cultural product, but in its economic dimension, as a merchandise.